2021
DOI: 10.1155/2021/8726388
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Final Irrigation Regimens on the Dentinal Tubule Penetration of Three Different Root Canal Sealers: A Confocal Laser Scanning Microscopy Study In Vitro

Abstract: This study evaluated the effects of different final irrigation regimens on the dentin tubule penetration of three different root canal sealers using confocal laser scanning microscopy (CLSM). A total of 160 single-rooted extracted mandibular premolar teeth were divided into five groups ( n = 32 each) according to the solution used in the final rinse protocol, as follows: 17% et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…According to the results of this study, we found that CHX irrigation showed the highest percentage of penetration in coronal sections as compared to others irrigants in both types of sealers (MTA fillapex -AH plus). Recently Zandi et al have shown that CHX can be used as a main irrigant, with similar success rates to those obtained with NaoCL (23) . Since, Rhodamine B dye was added to CHX to evaluate their penetration depth into dentinal tubules under confocal laser microscope, by mixing CHX with Rhodamine B the surface tension of CHX could be altered.…”
Section: Discussionmentioning
confidence: 68%
“…According to the results of this study, we found that CHX irrigation showed the highest percentage of penetration in coronal sections as compared to others irrigants in both types of sealers (MTA fillapex -AH plus). Recently Zandi et al have shown that CHX can be used as a main irrigant, with similar success rates to those obtained with NaoCL (23) . Since, Rhodamine B dye was added to CHX to evaluate their penetration depth into dentinal tubules under confocal laser microscope, by mixing CHX with Rhodamine B the surface tension of CHX could be altered.…”
Section: Discussionmentioning
confidence: 68%
“…However, CLSM was used in the current study to establish the depth of dentinal tubule penetration as it offers multiple advantages over the other methods. It can provide necessary information about sealer penetration within the root canal system along the dentinal tubule and allows the visualisation of depth and control of the depth by reducing or incising the background information from the focal plane, and is capable of assembling multiple optical sections despite of a thick section of specimen [ 34 , 35 ]. To evaluate dentinal tubule penetration, samples need to contain fluorescent dye.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, in the first case, it is conceivable that dust particles from drilling, inorganic filler particles or the insertion of the adhesive system can close dentinal tubules. Moreover, the smear layer cannot be completely removed and depends on the reagents and techniques used [32,33]. Occlusion can also occur via large molecules blocking tubules and/or absorption processes on the collagen fibers within the dentinal tubules.…”
Section: Elution Kinetics and Residual Dentin Thicknessmentioning
confidence: 99%